Study of the Effect Clay Substitution with Wood Sawdust and Hydroton on Compressive Strength, Density and Water Absorption of Red Brick Case Study of Traditional Red Brick Industry in Singgahan Village - Candra Fitrian, Raka; Sumarno, Agung (International Journal of Engineering, Science and Information Technology, 2021)
Redbrick is one of the building materials which is commonly used as a basic building material. In the traditional red brick factory in the village of Singgahan Tuban, East Java, some problems are often encountered in the field, namely red bricks that are cracked and broken on the bricks at the bottom of the pile. This has an impact on results that are not on target. The purpose of this study was to determine the effect of wood sawdust and hydroton substitution on the compressive strength, density, and water absorption capacity of redbrick. Using an experimental method with a substitution ratio of wood sawdust and hydroton of 5%, 10%, and 15%. Manufacture of 50 red bricks measuring 23 x 11 x 4.5 cm. The drying process is carried out for 5 days then burned at 900° C for 2 days. From the test, it was found that the red brick without substitution had a compressive strength value of 8.95 MPa, a density value of 1.59 grams / cm³, and a water absorption capacity of 11.14%. The red brick substitution of wood sawdust waste has a compressive strength value of 6.25 MPa, a density value of 1.48 grams / cm³ and a water absorption capacity of 12.04%. In the red brick, the hydroton substitution has a compressive strength value of 9.27 MPa, a density value of 1.64 grams/cm air, and a water absorption capacity of 11.22%.